Housing estate portal based on Internal Value Chain (IVC) Approach / Yeo Suat Hui - Yeo, Suat Hui (2002)
Internal Value Chain (IVC) is a well known marketing concept, proposed by Michael Porter of Harvard University, as a tool to identifying ways to create value. This concept has brought me the idea together with my knowledge of software development to develop a housing estate portal with IVC as the backbone to deliver customer value and satisfaction as well as supplier. Housing estate portal based on IVC approach will provide the basic features and functions liked others existing housing estate portal but will have some additional new features and functions that make the different between this portal and the existing portal. This is because all the features and functions and chose based on IVC that can add value to all the users. This research paper will includes the explanation of the system that introduces the four main modules or this system, including public module, virtual community module, developer module and supplier module, the objectives, scope and constraints of the project from the very first stage or system analysis, system design, development and integration till the testing phase, completing the software development life cycle. Reviews on various existing housing estate portal on the Internet and interview with the housing developer and supplier will also be available in this research paper. This report also discusses the tools that I am going to use to develop the housing estate portal. Time City Housing state Portal will be developed using Active Server Page with HTML and VBscript as the languages, and Microsoft SQL 2000 as the database server and Microsoft IISv5.0 as the web server running on Microsoft Window Server 2000 as the operating system platform, together with Three-Tier architecture design. It is hoped and believed that this system would be beneficial to all the users including the public, the developer and the supplier.